2015
DOI: 10.1007/s00468-015-1299-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced stem growth, but no reserve depletion or hydraulic impairment in beech suffering from long-term decline

Abstract: Keymessage Under non-extreme drought conditions, reduced stem growth is not associated with reserve or hydraulic impairment in beech suffering from longterm decline. Abstract Global change is expected to increase the frequency and the intensity of drought events in temperate ecosystems. In some regions, this might be associated with an increase in tree decline. Of the ecophysiological mechanisms that have been proposed to explain tree decline, an impairment of the vascular transport system and/or carbon functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…However, C allocation after drought remains largely unknown for trees under natural conditions. One of the few studies analyzing C allocation in mature trees after drought, found that the trunk sapwood and phloem NSC concentrations in Fagus sylvatica did not increase in a year of normal precipitation with regard to a previous dry year, although branch NSC concentrations did (Delaporte et al, 2016). However, growth recovery was found to be greater than the increase in branch NSC concentrations (Delaporte et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, C allocation after drought remains largely unknown for trees under natural conditions. One of the few studies analyzing C allocation in mature trees after drought, found that the trunk sapwood and phloem NSC concentrations in Fagus sylvatica did not increase in a year of normal precipitation with regard to a previous dry year, although branch NSC concentrations did (Delaporte et al, 2016). However, growth recovery was found to be greater than the increase in branch NSC concentrations (Delaporte et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…One of the few studies analyzing C allocation in mature trees after drought, found that the trunk sapwood and phloem NSC concentrations in Fagus sylvatica did not increase in a year of normal precipitation with regard to a previous dry year, although branch NSC concentrations did ( Delaporte et al, 2016 ). However, growth recovery was found to be greater than the increase in branch NSC concentrations ( Delaporte et al, 2016 ). While this study suggests that the rebuilt of storage after drought does not occur at the expens of growth, droughts could cause C storage reductions in other systems, particularly in isohydric species ( McDowell et al, 2008 , 2011 ; Brodribb et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in stem cavitation resistance under prolonged water deficit conditions (such as those observed in this study) are not a common functional response in many species (e.g. Martin -StPaul et al 2013;Delaporte et al 2015), but under certain water deficit conditions that permit continued albeit diminished expansive growth in sapwood tissues, this may eventually affect whole stem cavitation resistance. Further research is needed to understand the capacity for temporal changes in cavitation resistance in species experiencing long-term reductions in water availability (Anderegg 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Under optimal conditions, basal area growth curves increase almost monotonously, but later asymptotically with age. Decreasing trend usually appears when approaching the end of the individual beech tree's lifetime, therefore, clearly reduced stem growth rates can be a (predictive) sign of a longterm decline (Piovesan et al, 2008;Gillner et al, 2013;Delaporte et al, 2016). In comparison to other, especially to norther sites, some of the REZI trees underwent a drastic growth reduction, that could be interpreted as a predictive sign of vitality loss, which lead to drought-induced mortality event accounting also for the later sanitary interventions.…”
Section: Discussionmentioning
confidence: 98%